The nexus between Helicobacter pylori infection and anemia—a systematic review - Motupalli, Sankeerth Kumar; Oroszi, Terry L. (Frontiers in Hematology, 2024)
This systematic review delves into the intricate relationship between Helicobacter pylori (H. pylori) infection and anemia, shedding light on its significance for public health. Helicobacter pylori, a prevalent bacterium associated with gastritis, peptic ulcers, and stomach cancer, is examined alongside anemia, characterized by a deficiency in red blood cells or hemoglobin. Through an exploration of epidemiology, pathophysiological mechanisms, and healthcare implications, this review emphasizes the global distribution and incidence rates of H. pylori infections and anemia. Socioeconomic and environmental factors influencing prevalence are underscored. Diagnostic methodologies and treatment options for both conditions are discussed in detail. Analysis of studies investigating the causal relationship between H. pylori infection and anemia reveals potential mechanisms such as inflammation-induced alterations in iron and vitamin B12 absorption. While evidence suggests a connection between H. pylori infection and anemia, methodological limitations are acknowledged, necessitating further research to establish causality conclusively. The review highlights the importance of healthcare practitioners considering H. pylori screening for patients with unexplained or persistent anemia symptoms, as effective treatment of H. pylori infection may lead to improved anemia outcomes. Challenges such as antibiotic resistance and patient adherence to treatment regimens are identified. In conclusion, ongoing research into the link between H. pylori infection and anemia offers promising insights, albeit with persisting gaps in understanding. Collaborative efforts are required to address methodological challenges and develop tailored prevention and treatment strategies, accounting for variations in prevalence across populations and regions.